The Role of Notaries in Making International Grant Deeds: A Legal Study of Cross-Border Grant Regulations - Lubis, Ikhsan; Lubis, Duma Indah Sari; Lubis, Andi Hakim (Talenta Publisher, 2025)
Amidst the roaring tide of globalization, cross-border transactions—particularly in the realm of gifts—emerge as a landscape rife with legal challenges. A complex tapestry weaves itself from the threads of differing legal systems, document validity, and the unavoidable nuances of international recognition. In this arena, notaries stand as pillars of trust, ensuring that gift deeds transcend mere text to become legitimate statements acknowledged across jurisdictions. This study seeks to delve deeper into the role of notaries in crafting international gift deeds while identifying the hurdles they face: from bewildering regulatory differences and intricate tax provisions to the advent of underutilized new technologies. The research employs a normative legal approach, analyzing both national and international regulations. Law No. 2 of 2014 concerning Notary Services and the Hague Convention serve as lenses through which to comprehend how public documents achieve global recognition. Furthermore, legal principles such as lex loci celebrationis and the principle of mutual recognition are explored as foundations for resolving emerging cross-border legal issues. In conclusion, notaries play a vital role in upholding legal certainty in cross-border gift transactions. They are not merely navigators in a tumultuous sea of law but also connectors that bring clarity amidst confusion. It is recommended that notaries continually sharpen their skills and knowledge of international law as a proactive step to enhance services in an increasingly dynamic landscape of cross-border transactions.